Cultures of Resistance : Collective Action and Rationality in the Anti-Terror Age - Reynolds-Stenson, Heidi (Book collections on Project MUSE., 2022)
"Cultures of Resistance provides new insight on a long-standing question: whether government efforts to repress social movements produce a chilling effect on dissent, or backfire and spur greater mobilization. In recent decades, the U.S. government's repressive capacity has expanded dramatically, as the legal, technological, and bureaucratic tools wielded by agents of the state have become increasingly powerful. Today, more than ever, it is critical to understand how repression impacts the freedom to dissent and collectively express political grievances. Through analysis of activists' rich and often deeply moving experiences of repression and resistance, the book uncovers key group processes that shape how individuals understand, experience, and weigh these risks of participating in collective action. Qualitative and quantitative analyses demonstrate that, following experiences of state repression, the achievement or breakdown of these group processes, not the type or severity of repression experienced, best explain why some individuals persist while others disengage. In doing so, the book bridges prevailing theoretical divides in social movement research by illuminating how individual rationality is collectively constructed, mediated, and obscured by protest group culture"--